Apresentação PBCIB n. 1, v. 16, 2021 - Rodrigues Hermes de Araújo, Vania; Maria Freire, Isa; Freire, Gustavo Henrique de Araújo (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2021)
Apresentação PBCIB n. 1, v. 16, 2021